SIX SIGMA DMAIC ANALYSIS TO REDUCE VISUAL REJECT ON PLASTIC RAW MATERIALS IN LINE IQC SORTING USING SEVEN QUALITY TOOLS - Merjani, Abdullah; Yanti, Priska Putri; Redantan, Dadang (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2024)
In the era of globalization of trade, the key to increasing a company's competitiveness is quality. Only companies that are able to produce world-class quality products can win global competition. PT. INT Indonesia (Company name has been disguised according to company policy) is a company operating in the Electronic Component Manufacturing and Assembly industry located in Batam, Indonesia. PT. INT Indonesia produces semi-finished hearing aid products and microphones for aviation, firefighting, aerobics and other needs. PT. INT Indonesia supplies products and services to the hearing health and communications industries. Six Sigma is a method used to increase productivity and profitability. The steps in processing this data use the DMAIC (Define, Measure, Analyze, Improve, Control) stages. Results of overcoming visual over rejects on plastic raw materials with Six Sigma DMAIC analysis using Seven Quality Tools at IQC Sorting Line PT. INT Indonesia in this research brought changes for the better, it can be seen from DPMO = 11,355.6 from 1 million Quantity to DPMO = 4,190.7 from 1 million Quantity. And the initial Sigma level of 3.778σ becomes a Sigma level of 4.136σ.